Spectroscopic imaging of tin vapor near plasma threshold - D. J. Engels; H. K. Schubert; M. Kharbedia; W. Ubachs; O. O. Versolato (Physical Review Research)
We report on the spectroscopic imaging of tin vapors laser generated from thin liquid tin targets using laser intensities around the threshold of plasma formation. Specifically, we study tin vapor using an extinction imaging method in the UV regime (230–400 nm) to obtain 40-µm spatial-resolution images with 10-cm^{−1}-resolution spectra 100ns after vaporization. The vapor is created by irradiating a nonoxidized free-flying thin film with a nanosecond laser pulse, the intensity of which is varied between 1and130×10^{7}W/cm^{2}, from below to above the threshold of producing plasma. Vapors created with laser intensities below 40×10^{7}W/cm^{2} exhibit a spatially homogeneous neutral atomic component, with a temperature around 3000 K, as well as a broadband component due to nanoparticles. The morphology and composition of the vapor change as the plasma forms during vaporization at higher intensities, with the temperature of the vapor rising to 8000K at the highest intensity. At these intensities, the broadband component disappears, indicating that it is a vapor composed only of free atoms.